Mémoire des lieux, mémoires des hommes. Étude du portefeuille topographique « Beauce et Vendômois » de la collection Gaignières (1642-1715) - Clotilde Vivier (Les Cahiers de l'École du Louvre)
The collection of François-Roger de Gaignières (1642–1715) is carefully anchored geographically thanks to a number of topographical documents assembled in dedicated collections. The “Beauce and Vendôme” portfolio is a fine example of this, thanks to the richness and diversity its folios. It sheds light on the way Gaignières thought about space and made the territory an essential underpinning of his historical discourse. By distinguishing between different types of space (real, represented, imagined, that of the portfolio) and the way in which they combine to create a network of historical knowledge, invisible memories are brought to light, telling us something about the collector’s practice as a traveller. The portfolio also reveals the influence of Gaignières’ personal network on his historical vision. Historical documentation, personal memory and genealogical discourse thus intertwine around the monuments represented, giving them an unsuspected value and depth.